Content Marketing Strategy At Kedai Kopi Kebun To Increase Instagram Followers - Ida Rahma; Anisa Mutiah; Gladis Angle Aprilitab Malsiah Malau; Ngajudin Nugroho; Muhammad Syahrizal; Rizkah Fadillah (Citakonsultindo, 2026)
This study aims to analyze the content marketing strategies implemented by Kedai Kopi Kebun in increasing the number of followers on its official Instagram account. The background of this research is based on the phenomenon of increasing competition among coffee shops, which not only relies on product quality but also on the ability to utilize social media as a medium for promotion and communication with consumers. This study uses a qualitative approach. Qualitative research is a method that focuses on gaining a deep understanding of a phenomenon or problem by using descriptive (non-numerical) data such as text, video, or audio. Data collection techniques include interviews, observation, and documentation on the Instagram account @kedaikopi_kebun. The findings indicate that the content marketing strategies implemented include consistent posting, the use of visually engaging content, Storytelling through captions, the utilization of interactive features such as Instagram Stories and Reels, as well as collaborations with local influencers. These strategies have been proven to enhance audience engagement and contribute to the growth of followers. The study concludes that the implementation of appropriate content marketing strategies can be an essential factor in expanding marketing reach and strengthening brand image on social media.